Die Einführung der Christlichen Archäologie an der Universität Fribourg durch Johann Peter Kirsch - Studer-Karlen, Manuela (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2025)
The introduction of Christian archaeology at the University of Fribourg by Johann Peter Kirsch" - Within the landscape of German-speaking universities, the founding of the discipline of Christian archaeology at the University of Fribourg in 1890 represented an extraordinary innovation. The new academic field benefitted from its connection to the well-known archaeologist Giovanni Battista de Rossi, Johann Peter Kirsch’s teacher, on whose recommendation the latter was appointed as professor in Fribourg. With great knowledge of and enthusiasm for Christian archaeology, Kirsch came to stand for this subject area broadly. He was qualified in various subfields, such as epigraphy, iconography, catacombs, and the history of architecture. It was Kirsch’s record of scholarly achievement, as well as his enduring relationship with Rome, that enabled early Christian archaeology to achieve such a high reputation in Fribourg. The materials he used for teaching, which are still preserved in Fribourg today, shed light on his pedagogy, while his surviving correspondence documents his later contact with Fribourg from Rome. Kirsch was not only responsible for establishing and sustaining the discipline but also for locating a successor who would carry it forward.